How does the placement of a school matter ? Urban-centred English-medium Schooling and its Impact on Intergenerational Transmission of Gurung Language in Nepal - Sharma, Hari Maya (Advances in Social Sciences Research Journal, 2020)
This paper explores how urban-centred English-medium private schools in Nepal cause migration of young women with their children from remote village to urban and bring family as well as culture related problems which, ultimately, affect in the transmission of their language across generations. Visiting Chhimkekharka (i.e., a typical remote Gurung village located in the southern part of Tanahun District), listening stories of two migrant Gurung family cases in Aanboo Khaireni, and exploring experiences of some villagers via semi-structured interviews, this study found that English medium private schools which were centralised to Aanboo Khaireni had become the chief pull factor for the migration of Gurung young women with their children leading to change in family structure and cultural fluidity. Finally, it has created rupture in the intergenerational transfer of Gurung language across generations.